Parent–Child Career Congruence and Grit as Predictors of Career Decision Self-Efficacy among Low Socioeconomic Status High School Students - Hazatriningrum kusumawati; Rose Mini Agoes Salim (Universitas Ahmad Dahlan, 2026)
This study examined whether parent–child career congruence and grit predicted career decision self-efficacy among high school students from low socioeconomic backgrounds. A quantitative correlational design was applied, involving 146 twelfth-grade students selected through convenience sampling. Data were collected using standardized self-report scales measuring career decision self-efficacy, parent–child career congruence, and grit. The data were analyzed using multiple regression analysis in the Statistical Package for the Social Sciences software. The analysis results indicated that both parent–child career congruence and grit were significantly associated with career decision self-efficacy among economically disadvantaged students. The regression model showed an R2 value of .388, indicating that 38.8% of variability in career decision self-efficacy was explained by grit and parent-child career congruence. These findings highlighted the importance of aligned parental support and psychological perseverance in fostering adolescents’ confidence in making career decisions.